KARAKTERISTIK SEL RADANG BERDASARKAN KELAINAN LIPID PADA SUBJEK OBESITAS - Mus, Rosdiana; Aryandi, Rahmat; Ridwan, Asriyani (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2023)
Obesity increases the risk of type 2 Diabetes Mellitus (DM), cardiovascular disease and cardiometabolic risk which is characterized by lipid profile disorders (TG, DL, LDL and total cholesterol). In obesity, there will be excessive expansion of adipocytes and this will affect the mobilization of immune cells and the release of pro-inflammatory mediators such as the number of neutrophils, monocytes and lymphocytes circulating in the blood. The aim of the research is to assess the characteristics of inflammatory cells based on lipid abnormalities in obese subjects. The research method is a cross sectional design. Inclusion criteria were obese subjects (BMI>25 kg/m2, age 25-45 years, fasting 10-12 hours, not suffering from diabetes, heart disease or other inflammatory diseases and willing to be a subject). All subjects who meet the inclusion criteria will undergo sociodemographic interviews, anthropometric examinations and blood samples for automatic examination of inflammatory cells and lipid profiles using enzymatic methods. The results showed that there was a significant correlation between TG, LDL, and total cholesterol with neutrophils and Tg with monocytes.